15th Annual Fresno County Bar Association Judges' Dinner at Crossland's Barn - Watkins, Howard::::::::: (1983)
Tom Petersen, U.S. Magistrate Judge Alan Christensen, Oliver Jamison, Dan Jamison Coors beer cans; large mayonnaise tip jar on bar counter